2002
DOI: 10.1021/cm020087i
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, and Characterization of a New Second-Harmonic-Generating Tellurite:  Na2TeW2O9

Abstract: optical properties optical properties (excluding spectra) (solids and liquids) D 6000 -016Synthesis, Structure, and Characterization of a New SecondHarmonic-Generating Tellurite: Na 2 TeW 2 O 9 .-Polycrystalline samples of the title compound are prepared by solid state methods from stoichiometric amounts of Na 2 CO 3 , TeO 2 , and WO 3 (650 • C, 3 d). Single crystals are obtained hydrothermally from a solution of 3 M NaOH, WO 3 , and TeO 2 (autoclave, 470 • C, 48 h, 65% yield). As revealed by single crystal XR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
173
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 216 publications
(179 citation statements)
references
References 45 publications
6
173
0
Order By: Relevance
“…[38,39] We found that the local dipole moment of the BO 4 tetrahedra in Cs 2 B 4 SiO 9 is 7.44 Debye, which is much larger than that of other reported materials (0.005-0.727 Debye). [40] They are also larger than those of Cs1O 10 The electronic structure was studied by first-principle calculations.…”
Section: +mentioning
confidence: 54%
“…[38,39] We found that the local dipole moment of the BO 4 tetrahedra in Cs 2 B 4 SiO 9 is 7.44 Debye, which is much larger than that of other reported materials (0.005-0.727 Debye). [40] They are also larger than those of Cs1O 10 The electronic structure was studied by first-principle calculations.…”
Section: +mentioning
confidence: 54%
“…[26] A detailed description of the measurement was reported earlier. [27] Cs 2 I 4 O 11 has an SHG efficiency of approximately 300 SiO 2 . This efficiency is comparable to other NCS iodates, including HIO 3 (300 SiO 2 ), [26] LiIO 3 (300 SiO 2 ), [26] NdMoO 2 (IO 3 ) 4 (OH) (350 SiO 2 ), [28] and AMoO 3 (IO 3 ) (A = Rb or Cs, 400 SiO 2 ).…”
Section: +mentioning
confidence: 99%
“…We have previously published a structural model that allows us to calculate hd eff i calcd on the basis of metaloxygen bond hyperpolarizabilities b(MÀO). [27] With Cs 2 I 4 O 11 ,…”
Section: +mentioning
confidence: 99%
“…The particle size dependence on SH intensity shown in Fig. 5 reveals that the Gd x Bi 1Kx BO 3 phase has a phase matchable character [19].…”
Section: Surface Crystallization and Second Harmonic Generationmentioning
confidence: 88%